Service Quality Affecting the Clients’ Satisfaction with Administrative Agencies in Phra Nakhon Si Ayutthaya Province - supprasert, Theerasak; Amsa-ard, Phongsakorn; Niwes, Apichaya; Watanaputi, Adisai; Ruensook, Pinyada; Saensuk, Jantana; Plutiya, Kewalin (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The objectives of this research were 1. to study the service quality and satisfaction with administrative agencies in Phra Nakhon Si Ayutthaya Province, 2. to compare the clients’ satisfaction with administrative agencies in Phra Nakhon Si Ayutthaya Province, classified by personal factors, 3. to study the service quality affecting the clients’ satisfaction with administrative agencies in Phra Nakhon Si Ayutthaya Province. This study was quantitative research. The sample consisted of 400 clients requesting the service of administrative agencies in Phra Nakhon Si Ayutthaya Province, which were selected using a non-probability sampling through a convenience sampling. A questionnaire was used as a research instrument for data collection. Data were analyzed using statistics including frequency, percentage, mean, standard deviation, t-test, F-test and multiple regression analysis. The results of this research revealed that 1. overall service quality of administrative agencies in Phra Nakhon Si Ayutthaya Province was at a high level, and overall satisfaction of administrative agencies in Phra Nakhon Si Ayutthaya Province was at a high level 2. the results of comparing the clients’ satisfaction with administrative agencies by personal factors revealed that the respondents with different age, educational level, and occupation had different satisfaction with administrative agencies in Phra Nakhon Si Ayutthaya Province. In contrast, the respondents with different gender had indifferent satisfaction, and 3. from Multiple Regression Analysis, an aspect with the highest influence on the clients’ satisfaction with administrative agencies in Phra Nakhon Si Ayutthaya Province was Reliability, followed by Responsiveness, Assurance, Empathy, and Tangibles, respectively with statistical significance levels of 0.05 and 0.01.